Hubungan Antara Pengetahuan Ibu Bekerja, Jam Kerja Ibu Dan Dukungan Tempat Kerja Dengan Keberhasilan Pemberian Asi Eksklusif Di Wilayah Kerja Puskesmas Banyudono I - Rosyadi, Dina Wahyu, Yuli Kusumawati, S.KM, M.Kes (Epid), Kusuma Estu Werdani, SKM., M.Kes (2016)
Breast milk was the baby food was high in nutrients that were needed baby. World Health Organization (WHO) had recommended that babies exclusively breastfed until 6 months of age. According to the Demographic and Health Survey in 2012, Indonesia only had the scope of exclusive breastfeeding by 54,3% with the desired target was equal to 80%. The purpose of this study was to determine the relationship between knowledge of working mothers, mothers working hours and workplace support to the success of exclusive breastfeeding in Puskesmas Banyudono I. The study design used was cross sectional study. The population in this study 66 working mothers with babies 6-12 months. Sampling with random sampling, 54 mothers. Analysis of the relationship was done with statistical analysis Fisher exact test. Results showed mothers who are not exclusively breastfed as many as 48 people. The results of the bivariate analysis revealed no association between mother's knowledge to work with the success of exclusive breastfeeding in the region work of Puskesmas Banyudono I with p = 1.000. There was a relationship between mothers working hours with the success of exclusive breastfeeding in the PHC Banyudono Region I with p = 0.003. And there is an association between workplace support to the success of exclusive breastfeeding in the region work of Puskesmas Banyudono I with p = 0.044. The success of exclusive breastfeeding in mothers work is strongly influenced by the mother's working hours and workplace support